Report of a Rare Case of Spindle Cell Ameloblastic Carcinoma and the Diagnostic Utility of Immunohistochemistry. Issue 5 (May 2021) - Behtaj, Mohadese; Alawi, Faizan; Shanti, Rabie Mamdoh; Cannady, Steven; Zhang, Paul Jun; Modi, Mitul; Lamzabi, Ihab
Abstract : Ameloblastic carcinoma is a rare aggressive malignant epithelial odontogenic tumor. The spindle cell variant of ameloblastic carcinoma (SCAC) is exceedingly rare with 15 cases of SCAC having been reported. Therefore, because of the paucity of cases in literature related to SCAC, the biological behavior of the entity has not been well evaluated. Herein the authors report a case of incidentally diagnosed SCAC in a 20-year-old woman identified on imaging as part of the evaluation of a work-related facial injury. Histologically, the tumor had background of cystic ameloblastoma with areas of dense hypercellular spindle cells with short-to-long intersecting fascicles and occasional herringbone pattern intermixed with solid epithelial nests. Both the epithelial and spindle cells were positive for cytokeratin including cytokeratin 19, D2-40, and transducin-like enhancer of split proteins-1 immunohistochemical stains. The patient was followed for 18 months with no evidence of recurrence or metastasis. To the knowledge this is a first case of reporting D2-40 positivity in spindle ameloblastic carcinoma and this immunostain could be used as helpful marker to diagnose this entity.